ANALISIS KELAYAKAN USAHATANI BAYAM (Amaranthus Spp) DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANGANGGANG KOTA BANJARBARU - Irvani Rama Saputra (Chlorophyl, 2019)
The purpose of this research was to know the profit, the explicit cost, the implicit cost and feasibility analysis of spinach superior variety farming business